2019
DOI: 10.1016/j.heliyon.2019.e01985
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots derived from water hyacinth and their application as a sensor for pretilachlor

Abstract: Recently,carbon-based nanomaterials have been attracted much interest among the scientific community due to its extraordinary properties and applications. Mostly the fluorescent carbon nanomaterials are prepared from commercially available precursors. In this work, develop a new strategy for producing carbon nanoparticles (carbon dots) using phosphoric acid as an activating agent from water hyacinth present in Assam, India. These carbon nanoparticles show green fluorescence under UV light, and the sizes are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Additionally, pesticides that is widely found in water, soil, sewage sludge, sediment and aquatic biota increase the risk of different diseases such as mental confusion, eczema, reproductive toxicity, damage liver, kidney, neural and immune systems in human beings (Jayaraj et al, 2016). The detection of herbicide (pretilachlor) by C-Dots prepared from water hyacinth has also been reported (Deka et al, 2019). Wool-based microwaved assisted C-Dots sensor for detecting glyphosate based on the inner filter effect was also demonstrated .…”
Section: Sensing Of Pollutants and Toxic Chemicals In Foodmentioning
confidence: 99%
“…Additionally, pesticides that is widely found in water, soil, sewage sludge, sediment and aquatic biota increase the risk of different diseases such as mental confusion, eczema, reproductive toxicity, damage liver, kidney, neural and immune systems in human beings (Jayaraj et al, 2016). The detection of herbicide (pretilachlor) by C-Dots prepared from water hyacinth has also been reported (Deka et al, 2019). Wool-based microwaved assisted C-Dots sensor for detecting glyphosate based on the inner filter effect was also demonstrated .…”
Section: Sensing Of Pollutants and Toxic Chemicals In Foodmentioning
confidence: 99%
“…Most of the rapid detection of pesticides is achieved by monitoring their enzyme inhibition activity, however, a variety of pesticides can inhibit a particular enzyme leading to poor selectivity. However, with the recent development in 0-D nanomaterials, the interactions of pesticides with fluorescent CQDs have been reported to influence the fluorescence intensity depending upon the nature of interaction [51][52][53][54][55], which can be utilized as a transduction mechanism. Interaction of pesticides with CQDs leading to the perturbation of the recombination electronehole pair, different types of charge transfer, energy transfer, and IFE can lead to fluorescence change of CQDs.…”
Section: Detection Of Pesticidesmentioning
confidence: 99%
“…Conversely, Deka et al reported the detection of pretilachlor by enhancement of fluorescence of CQDs obtained from water hyacinth [52]. The enhancement of the fluorescence upon the interaction of CQDs with pretilachlor is reported to be also due to the electron transfer mechanism.…”
Section: Review Articlementioning
confidence: 99%
“…The absorbance at 275 nm is ascribed to the p-p* electronic transition of C]C and the n-p* electronic transition of C]O present on the PNDs surface. 56,57 The broad absorption extending between 330-350 nm is due to the presence of excited states of the functional groups on the surface. 58,59 One of the most remarkable characteristics of PNDs is their intrinsic photoluminescence property, which has an excitation-dependent uorescence spectrum with maximum uorescence intensity found when excited at 340 nm (Fig.…”
Section: Synthesis and Characterization Of The Synthesized Pndsmentioning
confidence: 99%